Policing the world: the practice of international and transnational policing - Casey, John (Carolina Academic Press)
Policing around the world : comparative policing -- National case studies -- Comparing policing strategies : international comparisons of policing strategies -- Responding to international and transnational crime : globalization, crime, and policing -- International structures of policing cooperation : the growth of international and transnational cooperation